2016
DOI: 10.3389/fimmu.2016.00232
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of CD8 T Cells Protective against Cytomegalovirus in a Mouse Model of Hematopoietic Cell Transplantation: Dynamics and Inessentiality of Epitope Immunodominance

Abstract: Successful reconstitution of cytomegalovirus (CMV)-specific CD8+ T cells by hematopoietic cell transplantation (HCT) gives a favorable prognosis for the control of CMV reactivation and prevention of CMV disease after hematoablative therapy of hematopoietic malignancies. In the transient immunocompromised state after HCT, pre-emptive cytoimmunotherapy with viral epitope-specific effector or memory CD8+ T cells is a promising option to speed up antiviral control. Despite high-coding capacity of CMVs and a broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 105 publications
4
41
0
Order By: Relevance
“…The idea that a contribution by L d -restricted CD8 + T cells is quantitatively or qualitatively critical for antiviral protection is also untenable in face of the finding that the infection is controlled in HvG-HCT in which the recipients cannot present L d -restricted antigenic peptides (Alterio de Goss et al, 1998;this report). Finally, protective activity of polyclonal mCMV-specific CD8 + T cells is so redundant that even deletion of immunodominant antigenic peptides presented by K d , D d , and L d is tolerated (Holtappels et al, 2008(Holtappels et al, , 2016Ebert et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…The idea that a contribution by L d -restricted CD8 + T cells is quantitatively or qualitatively critical for antiviral protection is also untenable in face of the finding that the infection is controlled in HvG-HCT in which the recipients cannot present L d -restricted antigenic peptides (Alterio de Goss et al, 1998;this report). Finally, protective activity of polyclonal mCMV-specific CD8 + T cells is so redundant that even deletion of immunodominant antigenic peptides presented by K d , D d , and L d is tolerated (Holtappels et al, 2008(Holtappels et al, , 2016Ebert et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Predictive algorithms to identify epitope insertion sites with optimized antigenic processing [42], have been recently applied to score peptide processing of natural and modified epitopes expressed by MCMV [43]. However, published data argue that the proteasome needs to cleave peptides very precisely behind the anchoring amino acid at the C-terminus of an epitope (reviewed in [44]), whereas additional amino acids present on the N-terminal end of the epitope precursor peptide may be trimmed by aminopeptidases upon TAP-mediated transport into the ER [45].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of adoptive T cells therapy, mortality can be prevented by transferring high doses of HSC into the host. By means of a recombinant virus in which four (BALB/c) immunodominant epitopes (IDEs) were functionally deleted, the Reddehase group elegantly showed that reconstitution of IDE-specific CD8 + T cells is not essential for antiviral control in infected HSCT hosts ( 80 ). Efficient protection in the absence of IDE was also evidenced in the CD8 + T cells adoptive transfer scenario ( 81 ).…”
Section: Cd8 + T Cell Immunotherapy Of CMV Diseasementioning
confidence: 99%